Ion beam bioengineering research - S. Anuntalabhochai (2018)
This new book summarizes recent progress of a newly developed novel bioengineering technology, namely low-energy ion beam bioengineering (IBB). Low-energy IBB has demonstrated powerful impacts and highly potential applications on biology, agriculture, horticulture and life science owing to multiple-factor interaction between energetic ions and biological organisms, as well as low-cost and convenience in operation. © 2011 by Nova Science Publishers, Inc. All rights reserved.